Prince Caspian / [the return to Narnia] - Lewis, C. S. (Clive Staples), 1898-1963.; Scofield, Paul, 1922-2008.; Suchet, Richard; Findlay, Freddie; Suchet, David; McCusker, Paul, 1958- ([S.l.] : Focus on the Family : Tyndale Entertainment, 2000)
Four children aid Prince Caspian and his army of Talking Beasts in freeing Narnia from evil.
Called back to Narnia -- The ruins of Cair Paravel -- Trumpkin the dwarf -- The old days -- Danger to the prince -- Talking beasts -- The council of lawn dancing -- Blowing Queen Susan's horn -- More then meets the eye -- Oh trees! wake won't you! -- The fords of Beruna -- What Lucy saw -- The return of the lion -- Woods on the move -- Sorcery and sudden vengeance -- The high king in command -- The combat of Miraz and Peter -- How all were very busy -- Reepicheep's wounds -- Aslan makes a door in the air -- Epilogue.
Compact disc.
Paul McCusker, director, adapter.
Paul Schofield (the storyteller) ; Richard Suchet (Prince Caspian) ; Freddie Findlay (Peter) ; David Suchet (Aslan) ; various other performers.
Keywords: Narnia (Imaginary place) -- Drama; Radio adaptations; Fantasy fiction